(untitled) (CIPEEX, 2025)
Introduction:Vulnerability and frailty in older adults represent complex challenges that demand a comprehensive approach to care. Early identification and intervention are essential to maintain autonomy, reduce risks, and promote quality of life.Objective:To describe the comprehensive geriatric assessment and care plan developed for an older adult with a functional frailty profile.Methodology:This is an experience report based on the application of assessment scales and the development of a multidisciplinary intervention plan. The evaluation encompassed physical, cognitive, social, and functional aspects, which are essential for understanding the overall condition of the older adult.Results:During the assessment, indicators of vulnerability, cognitive and functional deficits were observed, along with factors that increased fall risk and compromised performance in daily activities. Depressive symptoms, signs of sarcopenia, chronic pain, and visual limitations were also identified, all of which negatively impact independence.The scales applied indicated significant vulnerability (VES-13), high risk of functional frailty (IVCF-20), moderate cognitive impairment (MMSE), and limited social support. Difficulties were identified in both basic activities (such as bathing and locomotion) and instrumental activities (such as household organization and financial management).Discussion:The results underscored the need for interventions focused on reducing polypharmacy, minimizing environmental risks, and strengthening social support. The care plan included daily adaptations, such as guidance on a balanced diet, adequate hydration, and educational measures at home. Practical strategies were suggested, including decreasing salt intake, increasing the consumption of fruits and proteins, and engaging in simple physical exercises with light resistance.Conclusion:A multidisciplinary approach is essential for identifying and managing frailty in older adults. Individualized care, with referrals to geriatrics, nutrition, physiotherapy, and psychology, combined with periodic reviews of functional evolution, proved to be fundamental for promoting autonomy, reducing risks, and preventing complications. This experience reinforces the importance of coordinated and continuous interventions as strategies for active and healthy aging.